Ukraine calling : a kaleidoscope from Hromadske Radio 2016-2019 - Dyczok, Marta, 1963- (Ukrainian voices (Stuttgart, Germany), 2021)
"This book is like a time capsule. It's a selection of interviews that aired on Hromadske (Community) Radio's Ukraine Calling show. They capture what people were thinking during a critical time in the country's history, from the July 2016 NATO Summit through to Volodymyr Zelensky's 2019 landslide election victories. Decision makers, opinion makers, and others commented on events of the day and larger issues from politics to sports, religion, history, war, books, diplomacy, health, business, art and more. Interview guests include Canada's then Foreign Minister Chrystia Freeland, writer Andrey Kurkov, Crimean political prisoner Hennadii Afanasiev, UNHRC's Pablo Mateu, ethnologist Ihor Poshyvailo, and a cameo appearance by Boris Johnson. These interviews provide a unique, kaleidoscopic perspective on Ukraine as it was on the receiving end of a hybrid war from Russia." --